A Brief Analysis of Qi Haiyan’s Experience in the Diagnosis and Treatment of Thyroid Nodules Based on the Theory of “Pectoral Qi as the Foundation” - Xie, Yaqin; Qi, Haiyan (Journal of Contemporary Medical Practice, 2026)
Thyroid nodules are a prevalent endocrine disease encountered in clinical practice. Traditional Chinese medicine (TCM) exhibits unique advantages in holistic conditioning, nodule shrinkage, and relief of clinical symptoms. Rooted in Professor Mi Liehan’s academic proposition that “pectoral qi constitutes the foundation of the human body”, Professor Qi Haiyan proposes that dysregulation of pectoral qi and dysfunction of the qi pivot serve as the core pathological mechanisms of thyroid nodules. Her therapeutic strategy centers on the holistic principle of tonifying and regulating pectoral qi to restore the free movement of the qi pivot, supplemented by resolving phlegm and dissipating blood stasis, yielding remarkable clinical efficacy. This paper aims to summarize her clinical experience for reference in clinical management.